Circuit modeling for electromagnetic compatibility - Darney, Ian B. (SciTech Publishing, 2013)
The book reviews developments in the following fields: electromagnetic compatibility; lumped parameter models; transmission line models; antenna models; transient analysis; bench testing; and system design.